2011
DOI: 10.2337/db11-0416
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1–Mediated Cellular Metabolic Memory of High Glucose Via the LKB1/AMPK/ROS Pathway and Therapeutic Effects of Metformin

Abstract: Cellular metabolic memory occurs in diabetic microvascular and macrovascular complications, but the underlying mechanisms remain unclear. Here, we investigate the role of sirtuin 1 (SIRT1) and metformin in this phenomenon. In bovine retinal capillary endothelial cells (BRECs) and retinas of diabetic rats, the inflammatory gene, nuclear factor-κB (NF-κB), and the proapoptotic gene, Bax, induced by hyperglycemia, remained elevated after returning to normoglycemia. BRECs with small interfering RNA–mediated SIRT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 49 publications
8
183
1
8
Order By: Relevance
“…3e, f). To further verify that the transient exposure to high glucose (2 days) induced cellular metabolic memory in HRECs, we prolonged the high-glucose exposure time to 1 week and the total treatment time to 3 weeks, as in our previous study [14]. The results were consistent with the original test using the shorter high-glucose exposure time (ESM Fig.…”
Section: Screening Of Sirt1-targeting Mirnas In Diabetic Metabolic Mesupporting
confidence: 78%
See 3 more Smart Citations
“…3e, f). To further verify that the transient exposure to high glucose (2 days) induced cellular metabolic memory in HRECs, we prolonged the high-glucose exposure time to 1 week and the total treatment time to 3 weeks, as in our previous study [14]. The results were consistent with the original test using the shorter high-glucose exposure time (ESM Fig.…”
Section: Screening Of Sirt1-targeting Mirnas In Diabetic Metabolic Mesupporting
confidence: 78%
“…Mut, mutant increased 6 months later in STZ-induced diabetic rats [32], suggesting the persistent activation of inflammatory signalling pathways. Using the cell and rat models of metabolic memory induced by high glucose established in our previous study, we demonstrated that SIRT1 activation suppressed the cellular metabolic memory of high glucose in retinal endothelial cells by inhibiting the inflammatory gene NF-κB (also known as Rela) and the apoptosis gene Bax [14]. In the present study, Produced as small, non-protein-coding RNAs, miRNAs are endogenous regulators that play significant roles in many cellular processes [33,34].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Metformin, a commonly used anti-diabetic drug, decrease insulin resistance and hyperglycemia via inhibiting gluconeogenesis, hepatic glucose output and activation of free fatty acid oxidation in skeletal muscle [67]. Some of these beneficial effects of metformin were attributed to SIRT1 activation via AMPK pathway [68].…”
Section: Novel Therapeutic Agents Of Sirt1 Activators In Treatment Ofmentioning
confidence: 99%